Pelaksanaan Musyawarah Guru Mata Pelajaran Dalam Penjaminan Mutu Guru IPA SMP Di Kota Batu - Kurniatiningsih, Eka Putri; Widodo, Estu (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe; (1) TECPs implementation in quality assurance of Science teacher in Batu city, (2) the problem faced by TECP. The descriptive qualitative approach is used in this study. Chief of TECP, secretary and two members of TECP were used as samples in this study. Interview and documentation studies were used as the data collection technique. The result of the study shows that: (1) Implementation of TECP in the guarantee of Science teacher quality in Batu City is going well which is followed by 27 schools from Private and Public Junior High School or MTs. It also gets positive supports from the Batu Cityâ€™s Government (2) Problem faced by TECP in quality assurance of Science teachers in Batu City are the lack of teachers' presence participation, not maximal in deepening of the material competence of each teacher, and the gap relation of TECP participants. Problem-solving that TECP offer is focused on any activities which are related to their need. The most important thing is all about the routine meeting and continuity of this program. It is possible if the teachers join with another coaching outside the TECP such as workshops, seminars, etc. However, teachers should have the responsibility to acquire or learning more deeply about the material and vice versa, seniors should have a responsibility to take good care of the juniors to have good communication between each other in every step of activities.Keywords: Teacher Education Consensus Points or MGMP, quality of Science teacher in Batu CityÂ Abstrak: Penelitian ini bertujuan untuk mendeskripsikan; (1) Pelaksanaan MGMP dalam penjaminan mutu guru IPA di Kota Batu, (2) Problem yang dihadapi MGMP. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan jenis deskriptif. Responden dalam penelitian ini adalah ketua, sekretaris, dan dua anggota MGMP. Teknik pengumpulan data menggunakan teknik wawancara dan studi dokumen. Hasil penelitian menunjukkan bahwa: (1) Pelaksanaan MGMP dalam penjaminan mutu guru IPA di Kota Batu berjalan baik yang diikuti oleh 27 sekolah dari SMP/MTs Negeri dan Swasta serta MGMP mendapat dukungan positif dari Pemerintah Kota Batu (2) Problem yang dihadapi MGMP dalam penjaminan mutu guru IPA Di Kota Batu adalah kurangnya partisipasi kehadiran guru-guru, tidak maksimalnya kompetensi pendalaman materi dari masing-masing guru, dan adanya kesenjangan relasi peserta MGMP. Solusi MGMP adalah kegiatan MGMP harus sesuai dengan kebutuhan peserta, pertemuannya harus diadakan rutin, guru-guru dapat mengikuti pelatihan di luar, workshop, secara pribadi guru harus rajin belajar untuk pedalaman materi, dan sebaiknya para senior merangkul guru junior agar terjalin komunikasi yang baik disetiap kegiatan.Kata kunci: Musyawarah Guru Mata Pelajaran (MGMP), Mutu Guru IPA SMP di Kota BatuÂ